Outcome and Prognostic Factors of Surgically Treated Patients with Civilian Gunshot Wound to the Head in an Ethiopian Trauma Center - Temesgen, Melaku; Tadele, Abrham; Equar, Samuel; Worku, Metasebia; Yusuf, Aman; Bergene, Eyerusalem; Girma, Kalsidagn (WFNS Journal, 2025)
Background Cerebral gunshot wounds are among the most lethal forms of traumatic brain injury, with limited literature available from low-income countries. To the best of the authors' knowledge, no studies have been reported in Ethiopia. This study aims to review our experience, patterns, and outcomes of civilian gunshot injuries treated surgically at a major trauma center in Ethiopia's capital.Methods A single-institution, hospital-based study was conducted at a major trauma center in Ethiopia over 4 years (September 1, 2018–November 30, 2022). This study involved 42 patients with civilian gunshot wounds to the head who underwent surgical treatment. Postoperative functional outcomes were meticulously assessed using the Glasgow Outcome Scale Extended (GOSE), with comprehensive statistical analysis performed using SPSS version 27.0.Results Among the 42 patients included in this study, 83.3% were male, with a mean age of 26.7 years. Notably, 84% of patients presented to our hospital more than 24 hours postinjury, and 83% of injuries were attributed to interpersonal violence. Glasgow Coma Scale (GCS) scores at presentation ranged as follows: 14.3% of patients had a GCS of 3 to 8, 28.6% had a GCS of 9 to 13, and 57% had a GCS of 14 to 15. The overall mortality rate was 24%, while a favorable outcome, defined as a GOSE score greater than 4, was observed in 62% of patients. Significant prognostic factors for mortality included age over 30 years, a GCS score below 9, pupillary reaction abnormalities, higher Rotterdam computed tomography (CT) scores, bullet trajectory, and surgery duration exceeding 4 hours. Multivariate analysis identified age over 30 years, a GCS score below 9, and surgery duration exceeding 4 hours as significant predictors of unfavorable outcomes.Conclusion Cerebral gunshot wounds are associated with substantial mortality and morbidity. Our study highlights significant delays in reaching definitive care and identifies key prognostic factors such as age, GCS score, pupillary reaction, Rotterdam CT score, bullet trajectory, and duration of surgery. Targeted interventions and tailored surgical approaches could improve survival rates and functional outcomes for cerebral gunshot wounds. Moreover, violence prevention, rapid medical response, and investment in trauma care systems are crucial for enhancing patient outcomes, especially in low-income countries.
Keywords: gunshot wound to head; low income countries; prognosis; outcome